Exercise Management as a Predictor of Success in Extracurricular Activities among Junior High School Students in Medan - Dicky Hendrawan; Andi Sinsearif Zega; Andreas Diko Gunawan Tambunan; Angga Maulana; Andreas Matondang; Parlindungan Nababan (Ikatan Sarjana Olahraga Republik Indonesia (Kabupaten Kampar), 2025)
Objectives: This study aims to examine the correlation between exercise management and extracurricular achievements among junior high school students in Medan, Indonesia. The research seeks to assess how structured exercise routines influence students' performance in various extracurricular activities, such as sports, music, and academic clubs, and to identify mechanisms through which exercise management impacts students' success. Methods: A quantitative approach was used, involving 200 students (100 male and 100 female) from 10 junior high schools in Medan. Data were gathered using surveys to assess exercise management (frequency, intensity, duration, and consistency) and performance assessments in extracurricular activities. Statistical analysis, including Pearson’s correlation coefficient and regression analysis, was conducted to examine the relationship between exercise management and extracurricular achievements. Results: The study found a moderate to strong positive correlation (r = 0.68, p < 0.01) between exercise management and extracurricular achievements. Regression analysis revealed that exercise management accounted for 46.2% of the variance in extracurricular achievements. Students who engaged in structured physical exercise performed better in extracurricular activities, demonstrating improvements in discipline, time management, and teamwork. Conclusion: The study concludes that exercise management plays a significant role in improving students' performance in extracurricular activities. Schools should integrate structured physical activity into their extracurricular programs to enhance students' overall development. Further research should explore causal relationships and investigate additional factors influencing this connection.